Respuesta :
-3x+y=6
-3x-1\2 x+1=6
-3x-1\2 x = 6-1
-3x-1\2x = 5
-6x-1x \ 2 = 5 (taking LCM on left side)
-5x\2 = 5
-5x =5*2
-5x=10
x = -2 Answer
-3x-1\2 x+1=6
-3x-1\2 x = 6-1
-3x-1\2x = 5
-6x-1x \ 2 = 5 (taking LCM on left side)
-5x\2 = 5
-5x =5*2
-5x=10
x = -2 Answer
[tex] \left \{ {{y-3x=6} \atop {y+0,5x=-1}} \right. \\
\left \{ {{y-3x=6} \atop {-y-0,5x=1}} \right. \\
------\\
-3,5x=7\\
\left \{ {{-3,5x=7} \atop {y-3x=6}} \right. \\
\left \{ {{x=-2} \atop {y+6=6}} \right. \\\\
\left \{ {{x=-2} \atop {y=0}} \right. \\[/tex]
solution
x=-2
y=0
Maja
solution
x=-2
y=0
Maja